PENGURANGAN BULLWHIP EFFECT DENGAN MENGGUNAKAN METODE PERIODIC REVIEW PADA PT. SARI ROTI - Cyrilla Indri Parwati; Petrus Wisnubroto; Restu Aji Nur Kahfi (Universitas Sahid Surakarta, 2020)
The obstacle that is often encountered is the phenomenon of the bullwhip effect in the supply chain, this will hamper the supply chain itself. Bullwhip effect can occur due to high demand on upstream channels compared to downstream channels. The Yogyakarta sari juice distributor experienced product fluctuations in retailers, thus affecting the demand and inaccuracy of safety stock at retailers and also the central company. This research was conducted using the periodic review method, which is an effort to reduce information distortion on the supply chain chain, by collecting sales and order data from the company. The results of the product Sari sari bread in Pamella 1 for double soft bread in month 9 (12,842), month 10 (2,573), month 11 (0.051), peeled bread in month 9 (2.6832), month 10 (8,600), month 11 (1.00), 9th month sandwich (2989), 10th month (1,185), 11th month (1), 9th moon cream cheese sandwich (1,659), 10th month (1,434), 11th month (0,779). double soft bread in month 9 (0.784), month 10 (3,130), month 11 (1,965), peeled bread in month 9 (3,314), month 10 (1,340), month 11 (1,768), bread sandwich in month 9 (1,210), month 10 (1,445), month 11 (1,311), bread cream cheese sandwich 9th month (2,391), month 10 (1,340), month 11 (0.614). Retailer Atmaja double soft bread in 9 months (1964), month 10 (0.658), 11 months (2,898), 9 months peeled bread (1,667), 10 months (1,640), 11 months (4:00), types of moon chocolate sandwich 9 (2,204), month 10 (2,560), month 11 (1,887), bread cream cheese sandwich 9th month (2,045), month 10 (1,745), month 11 (1,398)